The Relationship of Age And Gender On The Incident of Chronic Supurative Otitis Media - Darussalam, Adam Ahmad; Abdullah, Adnan; Munandar As , Dhyas (Ahmad Dahlan Medical Journal, 2025)
Chronic Suppurative Otitis Media (CSOM) is an inflammation of the middle ear and part of the mastoid that persists for more than 2 months. It is characterized by tympanic membrane perforation and purulent discharge, occasionally mixed with blood. World Health Organization (WHO) data from 2004 indicates that CSOM affects 65-330 million people, with a higher prevalence in developing countries. This study aimed to investigate the relationship between gender and age with CSOM. The research employed an observational analytic method using secondary data from medical records at PKU Muhammadiyah Hospital Yogyakarta from January 1, 2020, to February 28, 2022. Subjects were selected using purposive sampling, resulting in 122 respondents. The analysis utilized univariate and bivariate analyses using chi-square. The results showed that among 122 patients with otitis media and CSOM, females (54.9%) outnumbered males (45.1%). Age distribution was as follows: 2.5% aged 0-5 years, 6.6% aged 6-11 years, 4.9% aged 12-16 years, 27% aged 17-25 years, 9.8% aged 26-35 years, 13.1% aged 46-55 years, 13.1% aged 56-65 years, and 13.1% aged over 65 years. Bivariate analysis revealed no significant relationship between gender and CSOM (r= -0.115, p= 0.206) or between age and CSOM (r= -0.081, p= 0.375). The study concludes that there is no significant association between age or gender and the occurrence of CSOM.